Enhancing Tsunami Warning Using P Wave Coda. Issue 10 (31st October 2019) - Lay, Thorne; Liu, Chengli; Kanamori, Hiroo
Abstract: Most large tsunamis are generated by earthquakes on offshore plate boundary megathrusts. The primary factors influencing tsunami excitation are the seismic moment, faulting geometry, and depth of the faulting. Efforts to provide rapid tsunami warning have emphasized seismic and geodetic methods for quickly determining the event size and faulting geometry. It remains difficult to evaluate the updip extent of rupture, which has significant impact on tsunami excitation. Teleseismic P waves can constrain this issue; slip under deep water generates strong pwP water reverberations that persist as ringing P coda after the direct P phases from the faulting have arrived. Event‐averaged P coda / P amplitude measures at large epicentral distances (>80°), tuned to the dominant periods of deep water pwP (~12–15 s), correlate well with independent models of whether slip extends to near the trench or not. Data at closer ranges (30° to 80°) reduce the time lag needed for inferring the updip extent of rupture to <15 min. Arrival of PP and PPP phases contaminates closer distance P coda measures, but this can be suppressed by azimuthal or distance binning of the measures. Narrowband spectral ratio measures and differential magnitude measures of P coda and direct P ( m B ) perform comparably to broader band root‐mean‐square (RMS) measures. P coda / P levels for large nonmegathrust events are also documented. Rapid measurement of P coda / P metrics after a large earthquake can supplement quick moment tensor determinations to enhance tsunami warnings; observation of large P coda levels indicates that shallow submarine rupture occurred and larger than typical tsunami (for given M W ) can be expected. Key Points: Teleseismic P coda amplitude generated by water reverberations ( pwP ) increases relative to the direct P for shallow slip under deep water Measurement of high or low P coda / P ratios in the distance range from 30° to 80° can reliably identify events with or without shallow slip Tsunami warning for subduction zone thrust earthquakes can be improved by rapidly measuring P coda to constrain the updip extent of slip